A comparative study of on-lay and preperitoneal mesh repair in the management of umbilical hernia - Panguluri, Adi Sukumar Nikhil Mehra; Komatreddy, Gagandeep Reddy; Venkat, Poojitha Reddy Gangam; Teja, Katra Sai (International Surgery Journal, 2022)
Background: Umbilical hernias can cause distress to the patients not only because of their complications but also because of the cosmetic angle, therefore this study was undertaken mainly to study the outcomes of preperitoneal mesh repair and on-lay mesh repair in the management of umbilical hernias. Methods: The present study was a prospective, observational and comparative study undertaken in the department of general surgery, who had been operated in Kamineni hospital LB Nagar, Hyderabad, Telangana, during a study period from November-2020 to September-2021. Results: Of 30 patients who underwent on-lay mesh repair, the mean hospital stay was 3.83±1.8 days; wound infection, seroma, hematoma, flap necrosis was seen in 1, 4, 2, 1 respectively and with no recurrence in 6 months follow-up. Of 30 patients who underwent pre-peritoneal mesh repair, the mean hospital stay was 2.13±0.63 days; Wound infection, seroma, hematoma, flap necrosis was seen in 0, 2, 1, 0 respectively and with no recurrence in 6 months follow-up. Conclusions: On-lay mesh repair can be replaced with preperitoneal mesh repair. Overall mesh related complications, including wound infection, seroma, hematoma, flap necrosis is quite rare. Less Hospital stay and low recurrence rate was observed in preperitoneal method. As wound complication increases risk of recurrence, procedures that do not result in formation of de-vascularizing flaps may be recommended.